Using claws to compare reproduction, stress and diet of female bearded and ringed seals in the Bering and Chukchi seas, Alaska, between 1953–1968 and 1998–2014. Issue 1 (6th January 2021) - Crain, Danielle D; Karpovich, Shawna A; Quakenbush, Lori; Polasek, Lori
Abstract : We investigate the relationship among reproduction, stress and diet in bearded and ringed seals by measuring hormones and stable isotopes stored in claws. As a result, we calculated pregnancy rate of individual females and found that ringed seals seem able to adjust well to changes in diet, unlike bearded seals. Abstract: Rapid climate warming is decreasing sea ice thickness, extent and duration. Marine mammals such as bearded ( Erignathus barbatus ) and ringed ( Pusa hispida ) seals, which use sea ice for pupping, molting and resting, may be negatively affected. Claws from bearded and ringed seals store up to 14 and 12 years of sequential analyte data, respectively. These data can be used to compare reproduction, stress and diet across decades. In this study, we compare progesterone, cortisol and carbon and nitrogen stable isotopes in female bearded and ringed seals during 1953–1968 (pre-1968, a period prior to sea ice decline) to 1998–2014 (post-1998, a period during sea ice decline). When comparing these periods, bearded seals had statistically higher cortisol concentrations post-1998, and for both species δ 13 C was more negative post-1998, while progesterone and δ 15 N did not change. There was a positive relationship between progesterone and cortisol Z-scores for both species, except for ringed seals post-1998. There was a negative relationship between cortisol Z-scores and δ 13 C for bearded seals evident in post-1998 indicating that higher cortisol Z-scores are associated with more negative δ 13 C in bearded seals in recent years. This negative relationship between cortisol and δ 13 C in bearded seals suggests a shift to higher prey diversity, possibly due to changes in sea ice in the Pacific Arctic evident post 1998. Progesterone Z-scores corresponded to expected differences among non-pregnant, unimplanted, implanted and post-partum individuals. Using these data, pregnancy history was determined for reproductive years for each individual female sampled, which could allow for yearly pregnancy rates to be calculated given a large enough representative sample of the population. These results combine decades of observational studies with hormones and stable isotopes to infer changes in reproduction, stress and diet, as well as the connection between these life history parameters.